Juniper smoke, skulls and wolves' tails. The Epipalaeolithic of the Anatolian plateau in its South-west Asian context; insights from Pınarbaşı. (1st November 2013) - Baird, Douglas; Asouti, Eleni; Astruc, Laurence; Baysal, Adnan; Baysal, Emma; Carruthers, Denise; Fairbairn, Andrew; Kabukcu, Ceren; Jenkins, Emma; Lorentz, Kirsi; Middleton, Caroline; Pearson, Jessica; et al.
<x xml:space="preserve">Abstract</x> This paper discusses the only substantive evidence for the Epipalaeolithic of central Anatolia. This evidence allows revised understandings of phenomena often proposed as characteristic of the Epipalaeolithic of South-west Asia including the appearance of sedentism, a putative Broad Spectrum Revolution, intensive plant exploitation and the emergence of distinctive ritual and symbolic practices. It also allows further evaluation of the effect of Late Glacial climate change on human behaviours.